Estimation of Broad-Scale Tradeoffs in Community Policing Policies. Issue 3 (12th October 2017) - Carson, Richard T.; Louviere, Jordan J.
Abstract : This paper looks at how to measure the tradeoffs in monetary terms that the public is prepared to make with respect to adoption of different community policing options. The approach advanced is a discrete choice experiment in which survey respondents face different policing options which can be described by a set of attributes ranging from costs to outcomes. The main contribution of this paper is to show how to go beyond the usual characterization of the monetized benefits of reducing the level of a specific type of crime to asking the question of whether those benefits differ depending on how that outcome is achieved.